XSOFT: estudo de reconhecimento, exploração e prevenção de vulnerabilidades de software através de uma distribuição LINUX - Rosa, Rafael Pereira [UNESP] (2010)
This work aims to give greater visibility to the issue of software security, due to people talk a lot in security conferences, that much of both IT (Information Technology) staff and, more specifically, IS (Information Security) staff does not know this, and, thanks to the spread of the mobile computing and of the cloud computing, this lack of deeper knowledge on this subject is increasingly becoming worrisome. It aims too, make applications to be developed in a security manner, priorizing the security of the information processed. It attempts to demonstrate the secure coding techniques, the principles of software security, the means to identify software vulnerabilities, the cutting-edge software exploitation techniques and the mechanisms of mitigation. Nowadays, the security guys are in charge of the most of the security tests in applications, audits and pentests, and it is undeniable that the so-called security experts, most often come from computer network field, having few experience in software development and programming. Therefore, the development process does not consider the security issue, thanks to the lack of knowledge on the subject by the developer, and the security tests could be improved whether security experts had a greater know-how on application development. Given this problem, the goal here is to integrate information security with software development, spreading out the process of secure software development. To achieve this, a Linux distribution with proof of concept applicati... (Complete abstract click electronic access below)